Smart Elastic Material with a Moving Local Stiffness Zone for Reducing the Effects of Impact Loading - Dai Zhao; Bartłomiej Dyniewicz; Czesław I. Bajer (Shock and Vibration)
The elastic material properties which change momentarily and locally under the high deformation rate due to the movement of a wavefront are presented. The work contains mathematical formulation, semianalytical results, numerical formulations, and simulation results demonstrating the effectiveness of modifying the rheological properties of the elastic material upon shock load or contact with a rigid obstacle. While the semianalytical solutions can be obtained in a narrow time interval, numerical solutions allow us to track the process of wavefront reflections from edges. The effectiveness of reducing the physical quantities significant for impact in the presented examples reaches 30–70% of forces or accelerations, depending on the adopted criteria.